2 - Healthcare Delivery and the Limits of the National Health Insurance Scheme in Nigeria - Asakitikpi, Alex E. (Africa Development, 2021)
Health reforms that target universal coverage have intensified in Nigeria since the dawn of the twenty-first century, and the National Health Insurance Scheme (NHIS), in particular, has been hailed as the panacea and appropriate framework for achieving the desired health for all by 2015. A few months to the target goal however, the reality is bleak and the task of reaching the goal more daunting than ever. This article provides a historical analysis of healthcare delivery in Nigeria Explanations for the difficulties in meeting health targets are discussed, pointing to weak governance, economic challenges, and socio-cultural contexts as important interacting factors slowing down the process. The aricle concludes by outlining some important emerging possibilities for strengthening the health system, including the liberalization of the health sector, enhancing public-private partnership, and suggestions for improving the National Health Insurance Scheme by recognizing key socio-cultural factors for inclusion in achieving health targets.